Multiport converters for incorporating solar photovoltaic system with battery storage: A pilot survey towards modern influences, challenges and future scenarios - Shanmugam, S.; Sharmila, A. (Frontiers in Energy Research, 2022)
The increasing significance of renewable power systems with diverse sources has produced an unexpected demand for electronic converters to integrate and simultaneously control, various energy resources, and storage devices. The voltage-current characteristics and the voltage levels of storage, as well as energy generating systems, are naturally diverse from those of loads. Hence, converters are employed to transform the energy from the renewable power plants to meet the total power demand, to enable the renewable energy system to use Maximum Power Point Tracking algorithm, to enhance the dynamic and static characteristics of the system, and to integrate the energy storage devices to resolve the issue of the irregularity of the load demand and unstable characteristics of the renewable sources. The implementation of a Multiport DC/DC converter (MDC) is a viable solution to increase the system efficiency and power density. The conventional MDC contains 1) DC unidirectional input ports to connect the renewable energy generating system; 2) two-way input ports to interface battery like storage devices; and 3) output ports to interface the load. Recently, numerous multiport converter configurations have been developed and described in the literature. Each of these reported MDCs has distinct architecture and working mechanism, which leads to a diverse level of intricacies, different component count, different performance, and reliability. This paper reviews various configurations of MDCs that have been introduced by different research communities to integrate solar energy with Battery Storage System (BSS). Different MDCs topologies such as partially-isolated, isolated, non-isolated configurations are discussed according to their physical structures and other aspects. This article can be employed as a guideline to select the appropriate configuration to match the certain condition of a system.